Comparison of obstetric to institutional antibiogram as an approach to advance antimicrobial stewardship in maternal care. (12th December 2022) - Boyd, Angela R.; Lewis, Ariana L.; Dallas, Steven; Xenakis, Elly; Ramsey, Patrick S.
Abstract: Objective: To create an antibiogram derived exclusively from our obstetric population and compare the clinical isolates and susceptibilities to our institutional antibiogram. Methods: Data collected by the University Hospital Clinical Microbiology Laboratory in SSC Soft from 01/01/2018 to 12/31/2018 was used to generate our institutional antibiogram. For comparison, we created an obstetric (OB) antibiogram using all clinical isolates collected during the same time interval from OB triage, labor & delivery, antepartum and postpartum wards. The antibiotic susceptibilities of the OB clinical isolates were compared to the institutional clinical isolates. Results: In total, we identified 929 clinical isolates from our OB population in 2018. Urine was the predominant source of clinical isolates (76.3%). The remaining sources included wound (10.1%), genital (9.0%), blood and other fluids (4.6%). Escherichia coli ( E. coli ) accounted for nearly half of all isolates (48.7%) followed by Group B Streptococcus (10.7%), Enterococcus spp. (9%), and Klebsiella pneumoniae (7.2%). There was no difference in susceptibilities of Gram-positive organisms in the OB antibiogram compared to the institutional antibiogram. Conversely, common Gram-negative organisms demonstrated less antibiotic resistance in the OB antibiogram compared to the institutional antibiogram. Escherichia coli, Klebsiella pneumoniae, and Proteus mirabilis were significantly more susceptible in the OB antibiogram compared to the institutional antibiogram to most antimicrobials tested. Conclusion: Compared to our institutional antibiogram, gram-negative clinical isolates in our OB population exhibit less antibiotic resistance. Creation of an OB-specific antibiogram, which more accurately reflects antibiotic resistance patterns within our unique patient population, may promote appropriate antimicrobial use by assisting in more informed antibiotic selection and limit unnecessary use of broad-spectrum antibiotics.